Commentary on the Special Issue on Moral Injury: Advances, Gaps in Literature, and Future Directions. Issue 3 (4th June 2019) - Neria, Yuval; Pickover, Alison
Abstract: We contextualize and provide commentary on articles in the current issue that address the nature, measurement, and consequences of exposure to potentially morally injurious events (PMIEs) and moral injury (MI). PMIEs involve acts of commission or omission of oneself and others and can include perpetration of, and failure to prevent, harm; MI includes "the lasting psychological, biological, spiritual, behavioral, and social impact of perpetrating, failing to prevent, or bearing witness to acts that transgress deeply held moral beliefs and expectations" (Litz et al., 2009). New and informative research aims to characterize types of PMIEs among military service members and veterans, including in multinational samples. There are also ongoing efforts to devise outcome scales that reliably capture broad MI outcome themes. Further, several new measures of MI assess emotional, cognitive, and behavioral responses of wrong‐doing; the nature of distress following PMIEs in civilians, servicemembers, and veterans; and interpersonal consequences in youth. These are promising efforts toward ecologically valid definitions of a potential MI phenotype. Notably, PMIEs may or may not meet DSM PTSD Criterion A, yet early longitudinal data reveal predictive and reciprocal effects of MI and PTSD on one another. Further, a growing literature on MI outcomes beyond PTSD is identifying ways in which MI is linked to alcohol misuse and self‐injurious behaviors. The sum of these efforts has led experts to consider the utility and shortcomings of extant PTSD interventions for individuals with MI. We address clinical implications of this emerging research domain, gaps in the literature, and future directions for research. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Comentario sobre el número especial sobre daño moral: avances, brechas en la literatura y direcciones futuras DAÑO MORAL: AVANCES, BRECHAS Y DIRECCIONES FUTURAS Contextualizamos y proporcionamos comentarios sobre los artículos en la edición actual que abordan la naturaleza, la medición y las consecuencias de la exposición a eventos potencialmente dañinos moralmente (PMIEs en sus siglas en inglés) y daño moral (DM). Los PMIEs implican actos de comisión u omisión de uno mismo y de los otros y pueden incluir la perpetración y la falla en la prevención, y daño; el DM incluye "el impacto duradero psicológico, biológico, espiritual, de comportamiento y social de perpetrar, no prevenir o dar testimonio de actos que transgreden creencias y expectativas morales profundamente arraigadas" (Litz et al. 2009). La investigación nueva e informativa tiene como objetivo caracterizar los tipos de PMIEs entre los miembros del servicio militar y los veteranos, incluso en muestras multinacionales. También hay esfuerzos continuos para diseñar escalas de resultados que capturen de manera confiable temas generales de resultados del DM. Además, varias medidas nuevas del DM evalúan las respuestas emocionales, cognitivas y conductuales de las malas acciones; la naturaleza de la angustia después de las PMIE en civiles, miembros del servicio y veteranos; y consecuencias interpersonales en la juventud. Estos son esfuerzos prometedores hacia definiciones ecológicamente válidas de un posible fenotipo del DM. En particular, los PMIE pueden o no cumplir con el Criterio A de TEPT, pero los datos longitudinales tempranos revelan efectos predictivos y recíprocos del DM y el TEPT entre sí. Además, una creciente literatura sobre resultados de DM más allá del TEPT está identificando formas en las que el DM está relacionado con el uso indebido de alcohol y las conductas autolesivas. La suma de estos esfuerzos ha llevado a los expertos a considerar la utilidad y las deficiencias de las intervenciones de TEPT existentes para las personas con DM. Abordamos las implicaciones clínicas de este dominio de investigación emergente, las brechas en la literatura y las direcciones futuras para la investigación. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Commentary on the Special Issue on Moral Injury: Advances, Gaps in Literature, and Future Directions Traditional Chinese 標題: 道德創傷特刊評論:文獻的進展、不足和未來研究方向 撮要: 今期的論文均探討潛在會導致道德創傷的事件經歷(PMIEs)及道德創傷(MI)的本質、測量、後果, 我們將對這些論文作評論。PMIEs包含自己和他人的委托或不履行行為, 當中包括傷害行為和無法避免傷害的行為。MI則包括「目擊違反其根深蒂固的道德信念和期望的犯罪行為、作出該等行為或無法避免該等行為所構成的心理、生物學、精神、行為、社會層面的長期影響」(Litz et al. 2009)。現在新的研究提供有用資訊, 旨在找出現役和退役軍人的PMIEs種類, 亦有採用多國樣本;亦一直有研究嘗試設計量表, 為求可靠地找出MI症狀的廣泛主題。再者, 有些新的MI測量法評估對犯錯行為的情緒、認知、行為反應, 平民、現役和退役軍人經歷PMIEs後的悲痛本質, 及青少年當中的人際後果。這些研究發現對得出潛在MI表型的生態有效定義有所幫助。值得留意的是, PMIEs有可能符合或不符合PTSD的診斷準則A, 但初期的縱貫數據反映MI 和 PTSD對彼此有預測和相互效應。再者, 越來越多文獻探討PTSD以外的MI, 檢視MI跟濫用酒精和自殘行為的關連。以上的研究, 鼓勵專家考慮長久以來對PTSD患者提供的干預治療, 對有MI的人士的功用和不足。我們亦探討這個新型研究範疇的臨床貢獻、目前文獻的不足之處, 以及未來的研究方向。 Simplified Chinese 标题: 道德创伤特刊评论:文献的进展、不足和未来研究方向 撮要: 今期的论文均探讨潜在会导致道德创伤的事件经历(PMIEs)及道德创伤(MI)的本质、测量、后果, 我们将对这些论文作评论。PMIEs包含自己和他人的委托或不履行行为, 当中包括伤害行为和无法避免伤害的行为。MI则包括「目击违反其根深蒂固的道德信念和期望的犯罪行为、作出该等行为或无法避免该等行为所构成的心理、生物学、精神、行为、社会层面的长期影响」(Litz et al. 2009)。现在新的研究提供有用信息, 旨在找出现役和退役军人的PMIEs种类, 亦有采用多国样本;亦一直有研究尝试设计量表, 为求可靠地找出MI症状的广泛主题。再者, 有些新的MI测量法评估对犯错行为的情绪、认知、行为反应, 平民、现役和退役军人经历PMIEs后的悲痛本质, 及青少年当中的人际后果。这些研究发现对得出潜在MI表型的生态有效定义有所帮助。值得留意的是, PMIEs有可能符合或不符合PTSD的诊断准则A, 但初期的纵贯数据反映MI 和 PTSD对彼此有预测和相互效应。再者, 越来越多文献探讨PTSD以外的MI, 检视MI跟滥用酒精和自残行为的关连。以上的研究, 鼓励专家考虑长久以来对PTSD患者提供的干预治疗, 对有MI的人士的功用和不足。我们亦探讨这个新型研究范畴的临床贡献、目前文献的不足之处, 以及未来的研究方向。